Blond hair, blue eyes, and "bad" Japanese: representing foreigner stereotypes in Japanese anime. Issue 3 (17th July 2020) - Ito, Rika; Bisila, Megan
Abstract: This paper investigates foreigners' linguistic and visual representations observed in 17 recent Japanese animated shows (or anime ), and explores ways to increase students' critical awareness of issues regarding Japanese language and culture. We find that foreign characters in anime tend to be linguistically represented with simplified, marked Japanese, and/or interjection of native language expressions to mark their otherness. While there are 17 countries represented in the anime shows we examined, the majority of foreign characters are Americans. Most of the characters are depicted as racially white and who speak marked Japanese. Of these, it is the American characters who are most often represented as white with blue eyes and blond hair, the quintessential representation of foreigners in Japan. Additionally, female characters account for only 20% of the total number of foreign characters, and many of them are visually sexualised. We discuss the effects of mediatisation regarding nihonjinron, 'the theory of Japanese', and propose ways to incorporate the findings into Japanese language instruction in order to increase critical awareness of issues regarding language and culture among students.